Biochemical criteria at 1 year are not robust indicators of response to ursodeoxycholic acid in early primary biliary cirrhosis: results from a 29‐year cohort study. Issue 11 (5th October 2013) - Papastergiou, V.; Tsochatzis, E. A.; Rodriquez‐Peralvarez, M.; Thalassinos, E.; Pieri, G.; Manousou, P.; Germani, G.; Rigamonti, C.; Arvaniti, V.; Karatapanis, S.; Burroughs, A. K.
Summary: Background: In primary biliary cirrhosis (PBC), biochemical criteria at 1 year are considered surrogates of response to ursodeoxycholic acid (UDCA). However, due to the slow natural history of PBC, evaluation at 1 year may be suboptimal to assess the therapeutic response, particularly in early disease. Aim: To determine whether evaluation of biochemical criteria at 1 year is a reliable surrogate of UDCA response in early PBC. Methods: We analysed the prospectively collected data of 215 patients (untreated = 129; UDCA‐treated = 86) with early PBC (normal baseline bilirubin/albumin) and a median follow‐up of 8 years (range: 1–29.1). The 1‐year attainment rates of the Barcelona, Paris‐I, Paris‐II and Toronto definitions, and their predictive relevance for a poor outcome (death, transplantation, complications of cirrhosis), were assessed either as a result of UDCA or no treatment. Independent associations with attaining each UDCA response definition were identified by multivariate analysis. Results: Untreated patients displayed 1‐year biochemical features compatible with 'treatment response' at rates (Barcelona: 36.4%, Paris‐I: 66.7%, Toronto: 59.7%, Paris‐II: 40.3%) similar to those obtained under UDCA. Depending on the definition, baseline ALP≤3xULN (OR: 4.80–35.90), AST≤2xULN (OR: 5.63–9.34) and early histological stage (OR: 3.67–3.87) were the stronger predictors for attaining the criteria. UDCA treatment was associated with attaining Barcelona (OR = 2.16) and Paris‐II (OR = 2.84), but not Paris‐I, and not Toronto definition when excluding late histological cases. Paris‐I criteria were significantly predictive of long‐term outcomes (HR = 2.83) in untreated patients. Conclusions: In early PBC, biochemical criteria at 1 year reflect severity of the disease rather than the therapeutic response to UDCA.